Soil Inorganic N Leaching in Edges of Different Forest Types Subject to High N Deposition Loads - Wuyts, Karen; De Schrijver, An; Staelens, Jeroen; Van Nevel, Lotte; Adriaenssens, Sandy; Verheyen, Kris (Ecosystems (New York), 2011)
We report on soil leaching of dissolved inorganic nitrogen (DIN) along transects across exposed edges of four coniferous and four deciduous forest stands. In a 64-m edge zone, DIN leaching below the main rooting zone was enhanced relative to the interior (at 128 m from the edge) by 21 and 14 kg N ha⁻¹ y⁻¹ in the coniferous and deciduous forest stands, respectively. However, the patterns of DIN leaching did not univocally reflect those of DIN throughfall deposition. DIN leaching in the first 20 m of the edges was lower than at 32-64 m from the edge (17 vs. 36 kg N ha⁻¹ y⁻¹ and 15 vs. 24 kg N ha⁻¹ y⁻¹ in the coniferous and deciduous forests, respectively). Nitrogen stocks in the mineral topsoil (0-30 cm) were, on average, 943 kg N ha⁻¹ higher at the outer edges than in the interior, indicating that N retention in the soil is probably one of the processes involved in the relatively low DIN leaching in the outer edges. We suggest that a complex of edge effects on biogeochemical processes occurs at the forest edges as a result of the interaction between microclimate, tree dynamics (growth and litterfall), and atmospheric deposition of N and base cations.